PERENCANAAN BIAYA DISTRIBUSI DENGAN MENGGUNAKAN METODE DISTRIBUTION REQUIREMENT PLANNING (DRP) UNTUK PRODUKSI MUR-BAUT DI PT. ASMAR NAKAMA PARTOGI 2014 (Jurnal Inovisi (Teknik Industri), 2017)
PT. Asmar Partogi Nakama is a company engaged in manufacturing of electroplating, one of the types of products produced by the process of electroplating is Nut-Bolt PT. Asmar Nakama Partogi not have a good distribution planning. Distribution planning undertaken by the company are less effective and have few weaknesses. Given these problems, the research conducted by the method of Distribution Requirement Planning (DRP) can be distributed in the hope especially Mur-Bolt products from the factory to each customer optimally.istribution Requirement Planning is a method to handle the procurement of supplies in a multi-echelon distribution network. The purpose of this study is to conduct cost planning and a good distribution of activity, so that success in meeting customer demand would be more optimal, increased sales performance in meeting orders on time and right amount so that distribution costs can be reduced seminimun possible. After calculating the cost of distribution for 2 years with the company method and DRP method, the total cost for using the company in the amount of Rp. 20.552.751 greater than the DRP method is equal to the difference Rp. 11.944.272 with the difference 41 %.Â Keywords: distribution requirement planning (DRP), optimal, production